Peran Efektifitas Key Opinion Leader dalam Membangun Citra Merek dan Niat Beli Fesyen Lokal - Sofia, Regina Deka; Gemilang, Galih (SAFE-Network, 2025)
Competition among local fashion brands in Indonesia is intensifying as consumer interest in local products and the widespread use of Key Opinion Leaders (KOLs) in digital marketing campaigns increases. This study aims to analyze the influence of familiarity, trustworthiness, and expertise on KOL effectiveness, as well as the influence of KOL effectiveness on brand image and purchase intention, with brand image as a mediating variable in the context of local Indonesian fashion brands in the Greater Jakarta area. The study used a quantitative approach with an online survey method to 155 respondents aged 17–40 years who had purchased fashion products from local brands in the past three months and had seen KOL recommendation content on social media. Data analysis was conducted using Structural Equation Modeling–Partial Least Square (SEM-PLS). The results showed that trustworthiness, familiarity, and expertise had a significant positive effect on KOL effectiveness. KOL effectiveness had a significant positive effect on brand image and purchase intention, while brand image had a significant positive effect on purchase intention. Brand image was proven to mediate the influence of KOL effectiveness on local fashion consumers' purchase intention. These findings underscore the importance of selecting credible, familiar, and competent KOLs in building a strong brand image and driving purchase intention in the Indonesian local fashion industry.